Rates of testing for BRCA mutations in young women are on the rise. (5th May 2016) - Barton, Mary Kay
Key Points: Genetic testing for BRCA mutations is increasing for young women, which is in keeping with current guidelines, and frequently affects treatment decisions. Adequate genetic counseling must be widely available for young women with breast cancer.